1990
DOI: 10.1161/01.atv.10.6.1082
|View full text |Cite
|
Sign up to set email alerts
|

Intimal lesion formation in rat carotid arteries after endothelial denudation in absence of medial injury.

Abstract: Injury of an artery by passage of a balloon catheter causes both endothelial denudation and medial damage and produces a marked smooth muscle cell (SMC) proliferative response. In this study, the endothelium from rat carotid arteries was removed by use of a rotating loop of 5/0 monofilament suture (gentle denudation technique), which did not cause any detectable damage to the underlying medial cells but did cause platelet adherence. Expression of platelet-derived growth factor (PDGF) A-chain and PDGF receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(102 citation statements)
references
References 17 publications
3
98
0
1
Order By: Relevance
“…This experiment was based on our experience with vascular injury models in which the magnitude of medial SMC proliferation correlates with the amount of damage (loss of DNA) inflicted on the vessel wall. 20,21 As we have previously shown, fibroblast growth factor-2 released from lethally and sublethally damaged cells is a key player in the onset of medial SMC proliferation. Nearly 37% of medial SMC were lost from the media within 2 days after ligation (ie, before SMC division occurs) in FVB/NJ carotid arteries, whereas no loss was detectable in the C3H/HeJ mice.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This experiment was based on our experience with vascular injury models in which the magnitude of medial SMC proliferation correlates with the amount of damage (loss of DNA) inflicted on the vessel wall. 20,21 As we have previously shown, fibroblast growth factor-2 released from lethally and sublethally damaged cells is a key player in the onset of medial SMC proliferation. Nearly 37% of medial SMC were lost from the media within 2 days after ligation (ie, before SMC division occurs) in FVB/NJ carotid arteries, whereas no loss was detectable in the C3H/HeJ mice.…”
Section: Discussionmentioning
confidence: 96%
“…20,21 We have also shown that the trauma-induced proliferation of SMC in the rat balloon injury model is mediated by the release of fibroblast growth factor-2 from damaged cells. 22,23 Furthermore, we have previously noted a loss of medial SMC in the carotid artery of FVB/NJ mice occurring within the first 2 days after ligation of the vessel.…”
Section: Loss Of Smc In Response Carotid Artery Ligationmentioning
confidence: 87%
“…(23). Various models of vascular injury have been introduced, including denudation of the endothelium by mechanical injury (wire, balloon catheters) (24,25). Luminal mechanical injury leads to endothelial denudation and platelet activation, which contribute to inflammatory cell recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Rat carotid arteries were injured using either the gentle injury technique previously described (32) or balloon catheter denudation. The catheter was introduced into the left common carotid through the left external branch and passed up and down the common carotid three times to ensure complete denudation.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure completely removes the endothelial cells lining the carotid artery and yet causes only a small increase (1.5%) in medial smooth muscle cell proliferation (32). Denudation is necessary because endothelialized arteries do not respond to systemic infusion of FGF2 (3).…”
Section: Response Of Arterial Smooth Muscle Cell To Exogenousmentioning
confidence: 99%